Augustinusregel, professio canonica und Prämonstratenser im 12. Jahrhundert. Das Beispiel der Norbert-Viten, Philipps von Harvengt und Anselms von Havelberg - Bomm, Werner (Regula Sancti Augustini. Normative Grundlage differenter Verbände im Mittelalter. Tagung der Akademie der Augustiner-Chorherren von Windesheim und des Sonderforschungsbereichs 537, Projekt C "Institutionelle Strukturen religiöser Orden im Mittelalter" vom 14. bis zum 16. Dezember 2000 in Dresden, 2002)
Keywords: 👤 anselm of havelberg; 👤 norbert of xanten; 👤 philip of harvengt

„Deo militans clericus“. Rittertum und Krieg im Werk Philipps von Harvengt - Leinsle, Ulrich G. (Analecta Praemonstratensia, 2001)
The view of knighthood and war in the work of Philipp of Harvengt is ambivalent. Essentially to a spiritual interpretation is the biblical typology (especially Ehud, David, Joshua, Judas Maccabaeus). Philipp does not dissolve the medieval class structure of the three ordines, but emphasizes the pre-eminence of the clergy. Chivalry has to serve the Church, which is quite usual for authors of the Gregorian Reform. However, a difference between class and behaviour can be observed regarding to both knights and monks. Monastic behaviour is transferred to the secular ideal of the miles litteratus; by literary education in the school, a knight becomes a clericus. Chivalry and war cannot simply be used as models of reflection in canonical life and spiritual warfare, while some knightly virtues, founded in biblical imagery, are important for the spiritual warfare in the monastery, especially bravery and obedience. Literary education and holiness are principles which superseded the rigid medieval class structure.
Keywords: 👤 philip of harvengt

Schola claustrum alterum dici debet. Filip van Harvengts raadgevingen aan studenten - Wouters, Jozef (Analecta Praemonstratensia, 2000)
In his letters to students, Philip of Harvengt († 1183) engages himself in a dialogue with the environment of the schools of his time. This is obvious since the exchange of letters was not an entirely private affair as it is nowadays. Letters were shared with one's companions and read by them. When Philip therefore wrote a letter to a student, he addressed in fact a broader public. The letters addressed to students appear to belong to two different literary types. His earliest letters, Ad Wedericum  and ad Hervardum  are in fact treatises concerning a debated question with some spiritual advise in the margin. Later written letters only contain spiritual advise. But all Philip's letters show a keen awareness of the fact that a sound exegesis starts from a litteral understanding of the material text of Sacred Scripture, even though he depicts its study as preparing for an experienced meeting with the  One who inspired it. This fundamental conviction concerning study of Scripture probably points towards influence from the Parisian school of the canons regular of Saint Victor. In his letter Ad Wedericum  Hugh of Saint Victor is explicitly quoted while Philip develops his argument in favour of a literal explication of the six days during which creation took place according to the book Genesis. "The school should be called another monastery", for, in spite of the different environment, assiduous study of Scripture is performed in both places. Bible study probably took on a different character in monasteries of  regular canons, such as Saint Victor in Paris and Bonne-Espérance, than the monastic lectio divina.
Keywords: 👤 philip of harvengt